2011
DOI: 10.1111/j.1749-4486.2011.02383.x
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term quality‐of‐life outcomes in children undergoing adenotonsillectomy for obstructive sleep apnoea: a longitudinal study

Abstract: Quality-of-life data are an important measure when deciding on a specific clinical intervention. In the short term, quality-of-life measures have been shown to improve after adenotonsillectomy for obstructive sleep apnoea. Our study demonstrates that the benefits of surgery are still persistent and the children continue to improve in the long term.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…Efficacy of adenotonsillectomy is modest in children with SDB and craniofacial abnormalities and/or neuromuscular disorders (class IV) [44,185,188,193,194,[214][215][216]. c) Quality of life improves post-adenotonsillectomy (class I and III, meta-analysis and systematic review) [111,113,126,178,211,217,218]. Evidence for the increase in growth rate and resolution of enuresis has been presented in two systematic reviews and in the CHAT study (class I) [109,110,180].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Efficacy of adenotonsillectomy is modest in children with SDB and craniofacial abnormalities and/or neuromuscular disorders (class IV) [44,185,188,193,194,[214][215][216]. c) Quality of life improves post-adenotonsillectomy (class I and III, meta-analysis and systematic review) [111,113,126,178,211,217,218]. Evidence for the increase in growth rate and resolution of enuresis has been presented in two systematic reviews and in the CHAT study (class I) [109,110,180].…”
Section: Literature Reviewmentioning
confidence: 99%
“…5 Additionally, studies have shown a significant objective quality-oflife benefit, both in the short and long term. 5,7 Diagnosis of OSA is made most accurately by the use of overnight polysomnography. 5 This, however, is both costly and time consuming, and in the UK management decisions are made predominantly on clinical grounds.…”
Section: Introductionmentioning
confidence: 99%
“…The gold standard test to diagnose SDB is polysomnography (PSG), which is an important tool to differentiate the various types of SDB (4,5). There is currently an unprecedented increase in the demand for testing for SDB due to an increasing awareness of pediatric sleep disorders, in particular, obesity-related OSA; the recognition of adverse consequences of SDB on cardiovascular, metabolic and neurobehavioural functions as well as the quality of life of children with SDB (6)(7)(8)(9)(10); and recommendations for preoperative monitoring with PSG for adenotonsillectomy surgery (10)(11)(12).…”
mentioning
confidence: 99%